GC-MS Analysis and Various In Vitro and In Vivo Pharmacological Potential of Habenaria plantaginea Lindl. (31st March 2022) - Mahnashi, Mater H.; Alqahtani, Yahya S.; Alyami, Bandar A.; Alqarni, Ali O.; Ahmed Alshrahili, Mohammad; Abou-Salim, Mahrous A.; Alqahtani, Mohammed N.; Mushtaq, Sadaf; Sadiq, Abdul; Jan, Muhammad Saeed
Abstract : Background . The current study aims to give a scientific origin for employing Habenaria plantaginea Lindl. as a potential candidate against nociception, inflammation, and pyrexia. The pharmacological studies were performed on crude extract and subfractions. In the gas chromatography-mass spectroscopy analysis, a total of 21 compounds were identified. The plant samples were displayed for in vitro anti-inflammatory potentials. The observed IC50 for chloroform against cyclooxygenase-2 and 5-lipoxygenase enzymes was 33.81 and 26.74 μ g/mL, respectively. The in vivo activities were prerequisites with the acute toxicity studies. In carrageenan-induced inflammation, the chloroform fraction exhibited 46.15% inhibition similar to that of standard drug diclofenac sodium 47.15%. Likewise, in the acetic acid-induced writhing test, the ethyl acetate fraction displayed 71.42% activity, which was dose-dependent as that of standard drug. In Brewer's yeast-induced antipyretic activity, a significant decrease in rectal volume was observed after 30, 60, and 90 minutes. Moreover, the results of this study indicated that the chloroform and ethyl acetate fractions inhibited nociception, inflammation, and pyrexia dose dependently. Likewise, mechanistic insights indicated that naloxone antagonized the antinociceptive effect of chloroform and ethyl acetate fractions, thereby signifying the involvement of opioidergic mechanisms respectively. These results suggest that these molecules present in this plant have synergistically beneficial potential for the cure and management of analgesia, inflammation, and pyrexia.